Kajian laporan penambahbaikan suruhanjaya pilihan raya: satu pandangan - Boyman, Siti Noranizahhafizah; Jawan, Jayum (UKM Press, 2013)
This article reviews the work and recommendations of the report of the Special Select Committee to Improve the Electoral Process which was established on 3 October 2011, with specific reference to the Improvement Report DR. 3 Year 2011 and DR. 1 Year 2012. Following an analysis of the above, this article also compare Malaysian electoral experiences with those of other countries in the region, and, as a result, concludes with recommendations to strengthen the electoral process in Malaysia.